Fitting the mixed Rasch model to the listening comprehension section of the IELTS: Identifying latent class differential item functioning - Effatpanah, Farshad; Baghaei, Purya; Ravand, Hamdollah; Kunina-Habenicht, Olga (Technische Universität Dortmund, 2024)
This study applied the Mixed Rasch Model (MRM) to the listening comprehension section of the International English Language Testing System (IELTS) to detect latent class differential item functioning (DIF) by exploring multiple profiles of second/foreign language listeners. Item responses of 462 examinees to an IELTS listening test were subjected to MRM analysis. Three classes emerged: (1) ‘Medium-level Stimulus Processors’ who can somewhat synchronize top-down and bottom-up processing, handle multitasking to a certain extent, comprehend moderately complex items, and manage input delivered at a relatively fast pace; (2) ‘High-level Stimulus Processors’ who have greater abilities in synchronizing top-down and bottom-up processing, multitasking, understanding complex items, and handling fast delivery input and more paraphrased content; and (3) ‘Low-level Stimulus Processors’ who rely more on bottom-up processing, have limited lexico-grammatical knowledge, struggle with multitasking and complex items, and find fast delivery input and paraphrased content challenging. Differences across the classes were further explained.
International journal of testing; 25(1)
Keywords: IELTS; Latent class differential item functioning; L2 listening comprehension; Mixed Rasch model; Multiple profiles; 360; 370; Rasch-Modell; Hörverstehen; International English Language Testing System